2019
DOI: 10.1002/lpor.201900070
|View full text |Cite
|
Sign up to set email alerts
|

High‐Speed Large‐Field Multifocal Illumination Fluorescence Microscopy

Abstract: Scanning optical microscopy techniques are commonly restricted to a sub‐millimeter field‐of‐view (FOV) or otherwise employ slow mechanical translation, limiting their applicability for imaging fast biological dynamics occurring over large areas. A rapid scanning large‐field multifocal illumination (LMI) fluorescence microscopy technique is devised based on a beam‐splitting grating and an acousto‐optic deflector synchronized with a high‐speed camera to attain real‐time fluorescence microscopy over a centimeter‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…S7, which demonstrates the mesoscopic imaging capability and the limitation of the current version of the CM 2 . The future generations of CM 2 will improve the light efficiency by exploring alternative designs, such as using novel focusing optics ( 12 ), diffractive optical elements ( 32 ), or fiber optics–coupled light sources ( 33 ). Second, the imaging optics of the CM 2 is designed by heuristically balancing several hardware and imaging attributes, including the resolution, FOV, image contrast, and device complexity and size.…”
Section: Discussionmentioning
confidence: 99%
“…S7, which demonstrates the mesoscopic imaging capability and the limitation of the current version of the CM 2 . The future generations of CM 2 will improve the light efficiency by exploring alternative designs, such as using novel focusing optics ( 12 ), diffractive optical elements ( 32 ), or fiber optics–coupled light sources ( 33 ). Second, the imaging optics of the CM 2 is designed by heuristically balancing several hardware and imaging attributes, including the resolution, FOV, image contrast, and device complexity and size.…”
Section: Discussionmentioning
confidence: 99%
“…The LMI fluorescence imaging system is based on a beam-splitting grating and an acoustooptic deflector, which are synchronized with a high speed camera to attain real-time fluorescence microscopy over a 20×20 mm FOV [29,30]. A 473 nm CW laser was used for h-FTAA excitation.…”
Section: Lmi Fluorescence Imaging System and Characterizationmentioning
confidence: 99%
“…The aim of the present study is to assess the selectivity and specificity of LCOs [28] for in vivo tauopathy detection in the P301L (Thy1.2) mouse model [16] with large-field multifocal illumination (LMI) fluorescence microscopy attaining 12×12 mm FOV and high spatial resolution (~6 m) [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Our recently developed LMI fluorescence imaging method based on a beam-splitting grating and an acousto-optic deflector synchronized with a high speed camera was employed for this study ( Fig. 1A) (35). Briefly, a high-repetition pulsed Q-switched, diode end-pumped Nd:YAG laser (model: IS8II-E, EdgeWave, Germany) operating at 532 nm wavelength was used for the excitation.…”
Section: In Vivo and Ex Vivo Lmi Fluorescence Imaging Of Aβ Deposits mentioning
confidence: 99%
“…We devised a large-field multi-focal illumination (LMI) fluorescence microscopy method that provides a unique combination between an extended 20 × 20 mm field-of-view as well as high spatial (~20 m) and temporal (10 Hz) resolutions (34,35). In the present study, we demonstrated whole brain mapping of Aβ deposits at single plaque resolution in APP/PS1 (26) and arcA (36) mouse models of AD cerebral amyloidosis mediated by HS-169 LCOs (37).…”
Section: Introductionmentioning
confidence: 99%